Movement-based co-creation of Adaptive Architecture - Schnädelbach, Holger; Arieyanto, Hendro (Springer, 2018)
Research in Ubiquitous Computing, Human Computer Interaction and Adaptive Architecture combine in the research of movement-based interaction with our environments. Despite movement capture technologies becoming commonplace, the design and the consequences for architecture of such interactions require further research. This paper combines previous research in this space with the development and evaluation of the MOVE research platform that allows the investigation of movement-based interactions in Adaptive Architecture. Using a Kinect motion sensor, MOVE tracks selected body movements of a person and allows the flexible mapping of those movements to the movement of prototype components. In this way, a person inside MOVE can immediately explore the creation of architectural form around them as they are created through the body. A sensitizing study with martial arts practitioners highlighted the potential use of MOVE as a training device, and it provided further insights into the approach and the specific implementation of the prototype. We discuss how the feedback loop between person and environment shapes and limits interaction, and how the selectiveness of this ‘mirror’ becomes useful in practice and training. We draw on previous work to describe movement based, architectural co-creation enabled by MOVE: 1) Designers of movement-based interaction embedded in Adaptive Architecture need to draw on and design around the correspondences between person and environment. 2) Inhabiting the created feedback loops result in an on-going form creation process that is egocentric as well as performative and embodied as well as without contact.